Modelo de gestión financiera para mejorar la rentabilidad de las mypes productoras de calzado en El Porvenir – Trujillo 2015 - Mendiburu Rojas, Jaime Alfonso (2019)
ABSTRACT The present investigation was developed with the objective of proposing a financial management model for shoe manufacturing companies in the El Porvenir-Trujillo district 2015 in order to improve the profitability of their companies. It was determined that the scientific problem is inadequate management of financial resources that prevents them from improving profitability. The sample was 132 mypes. The research was based on a mixed approach, not experimental, transversal, with a descriptive - correlational - propositive type of research, it was concluded that the relevance of proposing a financial management model for mypes is that this model contributes to perform a detailed analysis of the financial performance of the company using tools that allow diagnosing problems that are not visible in accounting figures, improving the process of making sound decisions that allow them to improve the profitability of it.